Recent Trends and Innovations in Elementary School Educational Game Development: A Literature Review - Atika, Syarifah (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2025)
Educational games have emerged as interactive learning media that enhance elementary students’ motivation, engagement, and understanding. This study analyzes recent trends in academic game development over the past five years by reviewing 15 peer-reviewed articles published between 2021 and 2025, sourced from Google Scholar. The analysis reveals that 60% of the studies focused on mobile-based games, particularly Android applications developed using Unity and Construct 2, due to their high accessibility and engaging interactive features. Additionally, web-based games such as Wordwall and desktop-based visual novel games developed with TyranoBuilder were found to improve students’ concept mastery by up to 30%, especially in language and mathematics learning. However, key challenges remain, including limited platform compatibility, the absence of adaptive learning features, and weak integration with formal curriculum standards. To enhance their effectiveness, future educational games should prioritize cross-platform accessibility, implement adaptive learning mechanisms, and ensure strong alignment with academic curricullum.